A critique on 'A Boltzmann transformation method for investigation of water vapour transport in building materials'. (November 2021) - Janssen, Hans
In 2011, this journal published the paper 'A Boltzmann transformation method for investigation of water vapour transport in building materials', proposing a dynamic measurement of building materials' vapour permeability via the Boltzmann-Matano method. This critique points out that this publication is flawed, since it proposes an invalid approach and presents erroneous results. The analysis first shows that the presented vapour permeability values cannot be reproduced and instead far lower vapour transport properties are obtained. These corrected outcomes are however also much below the dry-cup reference values, and it is established that these deviations stem from the invalidity of the proposed approach, due to disregarding the material's hygroscopicity. Given its erroneous results and invalid approach, it is finally recommended to have the paper officially retracted by the journal.